1994
DOI: 10.1021/es00056a017
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Hydrophobic Organic Compounds with Mineral-Bound Humic Substances

Abstract: 500 "c overnight prior to the sorption experiments. The BET surface areas determined by triple-point Nz(g) adsorption were 12.5 and 5.4 m2/g for kaolinite and hematite, respectively (Table 1). Peat humic acid (PHA), a well-characterized terrestrial humic substance from the International Humic Substances

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
222
3
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(252 citation statements)
references
References 50 publications
21
222
3
1
Order By: Relevance
“…However, in this study, it was found that there was no fixed proportionality between the log K exp p values at different ionic strengths. Murphy et al (1994) studied the influence of ionic strength, pH and cation valence on to the structure of mineral bound humic material. They found that increase in ionic strength brings out curling of humic material due to reduction in electrostatic repulsion between adjacent functional groups.…”
Section: Estimation Of Experimental Sorption Coefficientsmentioning
confidence: 99%
“…However, in this study, it was found that there was no fixed proportionality between the log K exp p values at different ionic strengths. Murphy et al (1994) studied the influence of ionic strength, pH and cation valence on to the structure of mineral bound humic material. They found that increase in ionic strength brings out curling of humic material due to reduction in electrostatic repulsion between adjacent functional groups.…”
Section: Estimation Of Experimental Sorption Coefficientsmentioning
confidence: 99%
“…The presence of calcium significantly influences the configuration of dissolved humic substances, which may in turn affect the structure of organic matter on the surface of solid particles and the sorption of HOCs to sorbents [26][27][28][29][30][40][41][42]. Ca 2+ can neutralize the negative charge of humic molecules and reduce the electrostatic repulsion between humic molecules, which may induce aggregate formation and generate an expanded structure with hydrophobic interior voids [24,29,30],…”
Section: Influence Of Ca 2+ Concentration On Phenanthrene Sorptionmentioning
confidence: 99%
“…In addition, the configuration change of humic substances in solution subsequently influences the structure of humics on mineral surfaces. Murphy et al determined the relative molecule size of dissolved humic acids in various solution by high-performance size exclusion chromatography (HPSEC) and found that dissolved humic acids exhibit loosen configuration at low I but relatively condensed structure at high I and the sorption capacities of HOCs to mineral-associated humic acids were larger at low I than at high I [27].…”
Section: Influence Of Ca 2+ Concentration On Phenanthrene Sorptionmentioning
confidence: 99%
See 2 more Smart Citations